Irremedial Work and Act‐Person Merger: Constructing Irredeemable Selves in Death Penalty Trials1. Issue 3 (16th May 2018) - Colomy, Paul; Phillips, Scott
Abstract : Irremedial work is an interpretive practice aimed at establishing a vital connection between a person's untoward behavior and his true self. Fifteen death penalty trial transcripts are employed as strategic research materials to examine how an individual's transgressions and the thoughts and feelings purportedly associated with his misconduct are merged with his self. A qualitative content analysis of these data identifies four recurring themes in the prosecution's efforts to fuse defendants' alleged crimes with their real selves: sacrilege, culpability, malevolence, and act‐person merger. The argument presented in this study can be extended by investigating bottom‐up irremedial work, the responses of those defined as irredeemable, and by considering cases where act‐person merger is experienced as an authentic expression of an individual's essential self.